The determinants of human resource information system success in Japanese manufacturing companies - Mohd Zin, Md. Lazim; Ibrahim, Hadziroh; Hassan, Zuraida (KODISA, 2016)
Purpose - The study sought to examine the relationship between individual characteristics and system features and Human Resource Information System (HRIS) success in Japanese manufacturing companies in Malaysia.Research Design, Data, and Methodology – This study adopt quantitative approach to investigate the relationship between individual characteristics and system features and HRIS.Toward this objective, a total of 700 questionnaires were mailed to a representative of the organization.A total of 187 questionnaires were returned, and only 145 were usable for further analysis, representing a response rate of 20.71%.Result - Results indicated that individual characteristics and two dimensions of system characteristics (ease of use and training) were significantly related to HRIS success.Unexpectedly, the results showed that the third dimension of system features (documentation) was unrelated to HRIS success.Conclusions - The results partially support the underlying arguments that individual characteristics and system characteristics have significant influences on HRIS success.The finding suggests that HRIS success in the organization can be generated as a result of good implementation of system support and employees’ readiness to apply HRIS in their jobs.